Are variations in PMSE intensity affected by energetic particle precipitation? - V. Barabash; S. Kirkwood; P. B. Chilson (Annales Geophysicae, 2002)
The correlation between variations in Polar Mesosphere Summer Echoes (PMSE) and variations in energetic particle precipitation is examined. PMSE were observed by the Esrange VHF MST Radar (ESRAD) at 67°53' N, 21°06' E. The 30 MHz riometer in Abisko (68°24' N, 18°54' E) registered radio wave absorption caused by ionization changes in response to energetic particle precipitation. The relationship between the linear PMSE intensity and the square of absorption has been estimated using the Pearson linear correlation and the Spearman rank correlation. The mean diurnal variation of the square of absorption and the linear PMSE intensity are highly correlated. However, their day-to-day variations show significant correlation only during the late evening hours. The correlation in late evening does not exceed 0.6. This indicates that varying ionization cannot be considered as a primary source of varying PMSE, and the high correlation found when mean diurnal variations are compared is likely a by-product of daily variations caused by other factors. Key words. Ionosphere (particle precipitation) Magnetospheric physics (energetic particles, precipitating) Meteorology and atmospheric dynamics (precipitation)